If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2a + 1) = 90 Reorder the terms: 6(1 + 2a) = 90 (1 * 6 + 2a * 6) = 90 (6 + 12a) = 90 Solving 6 + 12a = 90 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 12a = 90 + -6 Combine like terms: 6 + -6 = 0 0 + 12a = 90 + -6 12a = 90 + -6 Combine like terms: 90 + -6 = 84 12a = 84 Divide each side by '12'. a = 7 Simplifying a = 7
| (x+5)(3x-6)=0 | | 3x-5=-(x-4)+3 | | 5x+3=30 | | m(3m-4)(7-2m)=0 | | (11-4x)sqaured=0 | | 6(8/50) | | 6x-5y+15=0 | | (u-u^(1/2))(u+u^(1/2)) | | g=90+80 | | g=70+90 | | 1.2y=4-3y/2 | | 6x*ln(x)=0 | | 12-11a=5-a | | 8a+5=3a+14 | | 9a+3=7a+15 | | 6-5a=15 | | 14-2a=8 | | 4a-7=16 | | 12n+2=8n+15 | | 4(n-3)=21 | | 1-2y=4-3y/2 | | 2x/(x^2+7)^2 | | f(-5)=x^2+ax+b | | 5n^2-27n-18=0 | | a=p+pxt | | 1x^2+1x-42=0 | | r=p+pat | | 1n^2-16n+64=0 | | 1p^2-81=0 | | 1x^2+23x+90=0 | | (x^2-1)/x^2=0 | | 6n^2+34n+40=0 |